Initial serum MMP-9 activity as a bad prognostic factor after ischemic stroke - Kurzepa, Jacek; Bielewicz, Joanna; Kurczab, Paweł; Stelmasiak, Zbigniew; Stepulak, Andrzej (Current Problems of Psychiatry, 2011)
An early evaluation of ischemic stroke (IS) biomarkers enhances the chance for proper diagnosis and can predict the clinical outcome after acute phase of the disease. Our purpose was to evaluate the MMP-2 and MMP-9 serum activity as the prognostic factors for patients’ disability after IS. Finally, twenty patients with IS confirmed in computed tomography scans were prospectively enrolled into the study. The patients were examined by functional disability scales: Barthel Index (BI) and Modified Rankin Scale (mRS) at the admission and after 3 months from IS onset. The serum MMP-2 and MMP-9 activities were measured on the first day of stroke with use of gelatin zymography. BI scores increased and mRS decreased significantly after 3 months from the stroke onset in comparison with day 1 (p<0.05). Significant relationships between serum MMP-9 activity and late BI (r=-0.63, p=0.003) or mRS (r=0.67, p=0.002) scores, estimated at three months from the stroke, were noticed. In addition, we observed significant correlation between initial MMP-2 serum activity and late BI (r=-0.45, p=0.05). Our data indicated on serum MMP-9 rather than MMP-2 measured during acute phase of IS as a predictor of patients’ functional status three months after the stroke.